Nauki o polityce (także) jako dyscyplina nauk humanistycznych - Bogdan Szlachta (Ksiegarnia Akademicka Publishing, 2021)
In Poland political science has recently been classified as a part of the branch of social sciences. The aim of this paper is not to question the reasons behind such a categorization as the relation of political science (along with such disciplines as legal sciences and sociology) to social sciences is something obvious. However, I claim that it is worthwhile to reassess the arguments that provide for including political science also in the humanities. In addition to the tradition, the solutions adopted by other countries, and the Polish legal experiences, one should take into account an important research conducted by those political scientists who deal with history of political thought and contemporary political philosophy.